Contributing factors of consumer awareness on the roles of MyCC in enhancing consumer welfare: a study among consumer in Putrajaya / Noor Khalijah Mazlan - Mazlan, Noor Khalijah (2019)
The Malaysia Competition Commission (MyCC) was established on 1st April 2011.The MyCC came into force by virtue of the Competition Commission Act 2010 (CCA2010) on 1st January 2012. In 2017, the MyCC celebrated its 7th Anniversary. The objectives of the MyCC are to enhance consumer welfare, business practices and economic development. It has now been almost eight years that the MyCC came into existence and taking into account its enforcement activities and advocacy initiatives,there were only two studies conducted post three years of its existence related to impact study. The first baseline study was conducted in 2013 and the second study was the Study on awareness and perception of Competition Act 2010 (CA 2010) and the role of the MyCC in Malaysia which was conducted in 2016. However, both studies have something in common which is that the samples from both studies were not taken and conducted within the Putrajaya vicinity. Therefore, it is timely for the MyCC to conduct a study to examine the awareness level and factor on the role of the MyCC in the eyes of the consumers in Putrajaya. The target data samplings are consumers who work and reside in Putrajaya which includes the business community, government agencies, and students. This study is to determine consumer awareness on the role of the MyCC in improving consumer welfare, to determine the relationship between the factors of consumer awareness and the role of the MyCC in enhancing consumer welfare and to determine the most influential factor that contributes to the role of the MyCC in enhancing consumer welfare. For the purpose of gathering information, a set of questionnaire has been constructed. Moreover, the questionnaire has been validated by experts in the field of competition law. A total of There are 500 questionnaires in total that were provided and distributed to the consumers in Putrajaya. There are also several factors that have been determined in this study and those factors are advocacypro grammes, social media, and advertisements. For quantitative purposes Nevertheless,this study uses the Likert scale for data distribution which was included in the questionnaire. From the findings, it was found that the majority of respondents were neutral on consumer awareness on the role of the MyCC. The findings also show that there is a relationship between the factors of consumer awareness and the role of the MyCC in enhancing consumer welfare and it was also found that the highest factors relationship on the role of the MyCC in enhancing consumer welfare was advocacy programmes.